Speciálněpedagogická diagnostika oftalmopedická Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Röderová, Petra (Masaryk University Press, 2019)
Title in English: A special educational approach to Diagnostics of vision loss and visual perception deficits: Methodical texts for the MUNI 4.0 project The text acquaints the reader with the diagnostics of visual problems and visual impairment. The first part focuses on the classification and symptomatology of visual impairment, as well as on functional vision assessment. The specifics of diagnostics of visual impairments are also described in terms of specialist´s competences, support and intervention in pupils.